Analysis of heavy metal content in protein powders available on the Hungarian market: a reassuring snapshot, but not a reassuring quality guarantee - István László Horváth; Gyula Kajner; Gábor Galbács; Dezső Csupor (Journal of Nutritional Science)
Amateur and professional athletes often consume protein supplements to accelerate muscle gain; however, it has been suggested that these products not only are associated with risks when consumed excessively. Several recent reports have indicated that certain products are contaminated with heavy metals. Therefore, in this study, we aimed to investigate protein powders in Hungary for heavy metal contamination. A total of 22 commercially available protein powders (including whey, vegan, and beef based) were purchased on the internet for testing. We analysed the samples using laser-induced breakdown spectroscopy (LIBS) and inductively coupled plasma mass spectrometry (ICP-MS) to assess heavy metal contamination. The products were analysed for the presence of 16 elements (Be, Al, Cr, Mn, Co, Ni, Cu, As, Se, Rb, Cd, Sb, Cs, Ba, Hg, and Pb). The LIBS spectral analysis revealed the characteristics of the protein elements (C, C2, H, N, and O) and alkaline metals (Ca, Na, K, and Mg), which were consistent with the previous results. Neither LIBS nor ICP-MS measurements detected significant heavy metal content in the investigated samples above the limit specified in the regulations. Heavy metal contamination of protein supplements can be a serious health threat. Based on the varied results of the previous studies, it is prudent to include testing for heavy metals as part of the routine and mandatory quality control of these products.